Different Aspects of Letrozole Effect on Metabolism, Bone Health, Oxidative Stress and Prostate in the Intact Adult Dog - Zahra Dadvand; Dorsa Zahedtalab; Maryam Barzegar Bafruei; Nooshin Derakhshandeh; Asghar Mogheiseh; Saeed Nazifi; Mohammad Reza Divar; Mahboobeh Ashrafi (Veterinary Medicine and Science, 2025)
ABSTRACT Letrozole enhances male fertility by balancing oxidative stress and altering the hormonal regulation of spermatogenesis. The study aimed to determine the effect of short‐term letrozole administration on the concentration of canine prostatic‐specific esterase, parathormone, insulin‐like growth factor, vitamin D, alkaline phosphatase, lactate dehydrogenase, creatinine kinase, calcium, magnesium, cholesterol, and triglyceride in the serum of dogs. Moreover, total antioxidant capacity and lipid peroxidation were detected in intact adult dogs, serum, and seminal plasma. Seven intact adult male mixed‐breeds were given 0.25 mg/kg of letrozole orally daily for four weeks. Blood samples and sperm were collected on days 0 (pretreatment), 14 (treatment), 28 (treatment), and 42 (post‐treatment). During the trial, malondialdehyde concentrations in serum and seminal plasma dropped considerably between day 0 and days 28 and 42 and between day 14 and days 28 and 42. The calcium concentration fell considerably on day 42 compared to days 0, 14 and 28. The reduction in 1,25‐dihydroxy vitamin D concentration was significantly different on days 14 and 42. The concentration of parathormone and alkaline phosphatase rose during and after treatment. However, the insulin‐like growth factor diminished during letrozole administration. According to the current research, oral administration of letrozole has been demonstrated to have a negative impact on bone health, leading to elevated levels of parathormone and alkaline phosphatase, as well as reduced levels of serum IGF‐1, calcium, and 1,25‐dihydroxy vitamin D. Serum levels of canine lipid markers, including cholesterol and triglycerides, and creatine kinase and lactate dehydrogenase levels were unaffected. The low number of dogs and the brief observation period limit the validity of the results and the inferences that can be drawn from the study.